The Classification, for purposes of the calculation of taxable income, of land and assets incidental to land, that are used as trading stock - Wakefield, Yvonne (Department of Commercial Law, 2014)
In calculating the taxable income of a taxpayer, items of income and expenditure are classified as being either capital or revenue in nature, and are treated differently according to such classification. Over the years, a debate has emerged regarding the classification of items of income that are either part of the ground or accede to it, but which are treated by the taxpayer as trading stock. The debate extends to the classification of items of expenditure laid out in the production of income and for the purposes of trade, but which relate to land or things adhered to land. Items forming the subject matter of the discussion include sand, stone, coal, trees and other plants to be used not for the sale or use of their fruit, but for sale or use themselves